COMPONENTS FOR THE FORMATION OF ETHNIC COMPETENCE - Isomiddinov Asliddin Baxridin o'gli (Galaxy International Interdisciplinary Research Journal, 2023)
The concepts that enhance students' motivation to expand information about the history, culture, and origin of their people, to develop a sense of love and pride in their homeland, to preserve it, or to contribute to its development , We also highlighted the existence of common unity with other nations, the history and origins of the Turkish peoples, the promotion of ethnic competence, the understanding of different nations, and the strengthening of mutually friendly relations.